Non-suicidal self-injury and perfectionism in young adults : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Cory, Emily (Massey University, 2022)
Non-suicidal self-injury (NSSI) and perfectionism have each been foci of psychological research, however, the relationship between them has only recently begun to be examined. Further study is needed to understand if and how these concepts relate and the possible causal mechanisms underpinning this relationship. Discussion of the lived experiences of those who are perfectionistic and engage in NSSI also appears to be underrepresented in the literature. The current research, therefore, aims to examine the relationship between NSSI and perfectionism in young adults in New Zealand. The research also aims to examine the interpersonal theory of suicide (Joiner, 2005; Van Orden et al., 2010) to achieve a deeper understanding of the mechanisms of the relationship between NSSI and perfectionism. Using a two-stage data collection and analysis approach, New Zealand participants aged 18 to 35 years old first completed an online, self-report questionnaire to measure their engagement in NSSI, relative levels of perfectionism, and relative levels of thwarted belongingness and perceived burdensomeness. Secondly, a smaller subset of participants with a history of NSSI and experiences of perfectionism engaged in a semi-structured interview to discuss these experiences. Statistical analyses of the survey data supported overall perfectionism as positively related to NSSI. When perfectionism was broken down into two dimensions, both perfectionistic strivings and perfectionistic concerns were found to be positively related to NSSI. Overall perfectionism and perfectionistic concerns were both positively related to thwarted belongingness and perceived burdensomeness, while perfectionistic strivings was not. Thwarted belongingness and perceived burdensomeness were also positively related to NSSI. Finally, the relationship between both overall perfectionism and NSSI and perfectionistic concerns and NSSI were found to be partially mediated by perceived burdensomeness. The use of thematic analysis abstracted five main themes from the semi-structured interviews. These themes were: functions of NSSI; perfectionism and academic grades; perfectionism affected by others; NSSI scars and perfectionism; and failing to meet perfectionistic standards and engaging in NSSI. Overall, the current study found a positive relationship between perfectionism and NSSI and demonstrated that perceived burdensomeness may partially mediate this relationship. These findings may have important implications for clinicians working with individuals with perfectionism that engage in, or are at risk of engaging in, NSSI. Having an awareness of the above relationship may improve the implementation of targeted prevention, intervention and treatment methods resulting in better client outcomes. The current findings may also contribute to the future development of targeted prevention and intervention methods in this, and related areas.
Keywords: Self-injurious behavior; New Zealand; Perfectionism; Young adults; New Zealand; Psychology; 520302 Clinical psychology